Usabilidade do Repositório Institucional da UFMG em tempos de mobilidade digital - Karine Coutinho Drumond (2021)
There are many studies addressing usability of digital libraries and repositories, but there are still few adressing mobile access or studies considering the interaction and user experience on multiple devices. Although it seems to be unanimous among scholars the perception that mobile technologies can offer unique opportunities for greater people engagement, the use of mobile devices for the purpose of accessing, searching and retrieving information in digital repositories still needs more research. It is important to identify the interface adjustments to provide a better user experience. Among the research questions that need to be addressed, there are those related to interface adaptations, forms of navigation and information visualization and contents adaptation for better usability. The research has an interdisciplinary contribution, which proposes a dialogue between Information Science and Interaction Design, in the solution of the proposed research problem. The general objective of the research is to evaluate the usability and experience aspects of the users of the Repositório Institucional da UFMG, considering the use in two devices: the computer and the smartphone. The specific objectives are: 1) To identify the principles and recommendations for digital libraries project considering better user experience on mobile devices; 2) identify the limitations and characteristics of mobile devices and smartphones that influence the user experience; 3) identify the interface resources adopted by Repositório Institucional da UFMG that facilitate the search and user interaction; 4) evaluate the usability of the Repositório Institucional da UFMG and the users' satisfaction regarding the use via computer and smartphone; and 5) propose recommendations to improve usability and user experience. The research is a case study with an applied nature and has a qualitative approach in relation to the analysis of the problem. The environment for this study is the Repositório Institucional da UFMG. The project will include three methodological procedures: (1) systematic literature review; (2) interface evaluation of Repositório Institucional da UFMG; (3) and empirical study with users. The theoretical conceptual foundation addresses digital libraries and repositories, usability, design and human-computer interaction, search behavior in digital media and the use of mobile devices. The results achieved include the identification of the main usability problems of the UFMG Repository, as well as proposing recommendations for improvements and identifying future opportunities.